Grace, Syntax I and Syntax II scores as predictors of one-year MACE outcome in patients treated with percutaneous coronary intervention - Davidović, Aleksandar; Cvijanović, Dane; Davidović, Jelica; Lazić, Snežana; Lazić, Bratislav; Čučić, Luka; Milić, Marija; Marković Nikolić, Nataša (Vojnosanitetski pregled, 2022)
A prospective, observational, cohort study made it possible to monitor the clinical parameters of the GRACE, SYNTAX I and II scores. The study included 400 patients diagnosed with AMI, treated and followed for one year . A statistically significant high degree of correlation was observed between the GRACE with the SYNTAX I and the SYNTAX II score (rho> 0.5; p = 0.001). Regression analysis of the GRACE score showed that a higher GRACE was a significant predictor of higher SYNTAX I and II scores in the entire sample of patients diagnosed with AMI treated with PCI in patients with STEMI , while this was not observed in the group of patients with NSTEMI. The GRACE was identified as the optimal value for predicting MACE outcomes with a sensitivity of 74.5% and a specificity of 61.6%. The SYNTAX I with an accuracy of 89.1% predicted (AUC = 0,89; 95% IP = 0,84–0,93; p = 0,001)) the occurrence of MACE outcomes in our patients. The SYNTAX I was identified as the optimal value for predicting MACE outcomes with a sensitivity of 86.3% and a specificity of 79.4%. The SYNTAX II explained the occurrence of MACE outcomes in 90.5% of our subjects (AUC = 0.9; 95% IP 0.89; p = 0.001). The SYNTAX II value was identified as the optimal value for predicting MACE outcomes with a sensitivity of 88.2% and a specificity of 76.8%. Conclusion: GRACE, SYNTAX I and II scores in patients with AIM who underwent PKI are independent and strong predictors of MACE outcomes intrahospitally but also over a period of one year.